Toward a Blue Economy : A Promise for Sustainable Growth in the Caribbean - Patil, Pawan G.; Virdin, John; Diez, Sylvia Michele; Roberts, Julian; Singh, Asha (World Bank, Washington, DC, 2016)
The report is structured in four chapters that together, responds to the fundamental questions raised by decision-makers within finance ministries and central banks across the Caribbean. Chapter one provides a working definition of the ocean economy and the blue economy concepts, and explains why these terms are growing in importance globally and specifically across the Caribbean. Chapter two deconstructs the ocean economy, suggesting that a significant portion of the economic value derived from the ocean is based on the natural resources and ecological systems that function in economic terms as the ocean economy’s natural capital asset base. Chapter three attempts to reconcile two global and Caribbean region-specific trends, a growing ocean economy and declining natural capital asset base, and suggests that reformed and integrated policy packages are necessary for sustainable development of countries’ ocean space and long-term growth from their ocean economies. Chapter four offers an approach for consideration by decision-makers to serve as a guide in enabling a transition toward a Caribbean blue economy.